TRANSFORMASI BERPIKIR ALJABAR DAN KALKULUS MAHASISWA MATEMATIKA DALAM MENYELESAIKAN MASALAH PERSAMAAN DIFERENSIAL - Arjudin; Sripatmi; Muhammad Turmuzi; Dwi Novitasari; Ratih Ayu Apsari (MaPan : Jurnal Matematika dan Pembelajaran, 2022)
This study aims to analyze the transformation of algebraic thinking and calculus of preservice the mathematics students based on SOLO taxonomy in solving differential equations problems. The research subjects were 86 students in the mathematics education study program. Subject selection uses purposive sampling (students who take courses in differential equations). Data were collected using problem-solving tests and interviews which were then analyzed using the descriptive qualitative method with the following stages: (1) transcribing test and interview data, (2) coding segmentation, (3) analyzing student thinking transformations, and (4) concluding. The results showed that the transformation of algebraic and calculus thinking was used by students at each level of thinking to solve problems. The higher the level of thinking achieved, the better and the maximum transformation of algebraic and calculus thinking used by students. These results indicate that students need to be well supported and facilitated in problem-solving to achieve higher levels of thinking, such as the relational and extended abstract levels.